2010
DOI: 10.1590/s0100-40422010000100028
|View full text |Cite
|
Sign up to set email alerts
|

Tecnologia de nanocristais em fármacos

Abstract: Recebido em 22/10/08; aceito em 28/5/09; publicado na web em 8/12/09 NANOCRYSTAL TECHNOLOGY IN PHARMACEUTICALS. The use of poorly water soluble molecules in pharmaceutical area has grown. Since these molecules exhibit low oral bioavailability, they are not used in intravenous administrations. Therefore, it is necessary to develop their new formulations with the aim to increase their oral bioavailabilities as to enable intravenous applications. One of the few possibilities in achieving this is a nanonization pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
16

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 25 publications
0
5
0
16
Order By: Relevance
“…In a group of mice treated with dose of 5 mg/kg, 90% survival was observed during 9 days, compared to 60% survival in the control group. 71,73 It was previously demonstrated that P-MAPA exhibited antiviral activities against Stomatitis vesicular virus, Poliovirus 3, Herpes virus type 1, and Adenovirus type 5. 63 An i.p.…”
Section: Phosphate Accumulation In Organismsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a group of mice treated with dose of 5 mg/kg, 90% survival was observed during 9 days, compared to 60% survival in the control group. 71,73 It was previously demonstrated that P-MAPA exhibited antiviral activities against Stomatitis vesicular virus, Poliovirus 3, Herpes virus type 1, and Adenovirus type 5. 63 An i.p.…”
Section: Phosphate Accumulation In Organismsmentioning
confidence: 99%
“…The histopathology results showed the effectiveness of DMBA in pancreatic cancer in the rats, as well as progressive tissue repair, particularly in the presence of P-MAPA, during therapeutic treatment. 89 It interesting that P-MAPA was also observed as a nanosized structure upon nanoprecipitation in dimethyl sulfoxide and water, 70,73,79 by high pressure homogenization and by ultrasound in the presence of Pluronic F68 and coating with chitosan. 75,80,81,[90][91][92][93][94][95] Nanonization is a top-down process, i.e.…”
Section: Phosphate Accumulation In Organismsmentioning
confidence: 99%
“…7,9 Por sua vez, os nanocristais representam uma estratégia de nanomização de fármacos pouco solúveis em água, de forma a aumentar a biodisponibilidade e propiciar vias de administração injetáveis. 10 …”
Section: Tipos De Nanocarreadores Biodegradáveisunclassified
“…Uma vantagem em relação às nanopartículas poliméricas é a não utilização de matrizes poliméricas. 10 O comprimido com o imunossupressor sirolimus (Rapamune ® , Wyeth Pharmaceuticals) foi o primeiro produto comercial disponível no mercado, aprovado em 2000. Alguns outros medicamentos foram re-desenvolvidos empregando a tecnologia NanoCrystal ® para uma maior biodisponibilidade e uma menor variação das concentrações plasmáticas do fármaco, quando o paciente está em jejum ou alimentado, como o fenofibrato (Tricor ® , Abbott), verapamil (Verelan ® , Alkermes Pharma) e o metilfenidato (Ritalin LA ® , Novartis).…”
Section: Nanocristaisunclassified
“…São exemplos a afidicolina, a violaceína e o Proteic -Magnesium Ammonium Phospholinoleate Anhydride ou P-MAPA (Figura 1). 1,2 A biodisponibilidade do fármaco é influenciada por diversos fatores como a velocidade de dissolução, tamanho da partícula, área superficial, polimorfismo do fármaco, formação de sais, permeabilidade, lipofilia, pKa. 3,4 No caso de fármacos insolúveis, a biodisponibilidade pode ser melhorada através da micronização da matéria--prima, que promove o aumento da sua área superficial.…”
Section: Introductionunclassified